Upaya peningkatan kedisiplinan guru dalam mengajar di SD Jolosutro melalui penerapan reward and punishment - Sunaryati Sunaryati; kristina kristina (Borobudur Educational Review, 2022)
Efforts to improve the quality of education of the Indonesian nation in accordance with the ideals of the nation stated in the preamble of the 1945 Constitution, to realize the general welfare and intelligence of the nation's life, education has an important role in increasing piety to God Almighty. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education through formal education, basic education and secondary education. Optimizing this requires special attention, namely implementing a reward and punishment strategy for teachers. The method used is Planning, Action, Observation, and Reflection which is carried out in 2 cycles, each cycle has 2 observation meetings. The respondents of this study were 6 affiliated teachers at SD N Jolosutro. The results showed that the pre-cycle teacher discipline assessment of 15 there were 8 indicators (53.3%) that had reached the criteria of success indicators and there were 7 indicators (46.7%) that had not been completed. Observations in cycle 1, meetings 1 and 2 show that meeting 1 obtained a score of 72.8% which is still below the minimum criteria, while the second meeting has met the criteria for success indicators, which is 75.7%. However, the level of discipline is still lacking so it is still need to be re-observed. Observations in the second cycle of meeting 1 obtained a value of 81.9% while the second meeting also obtained a value of 87.2%. The application of reward and punishment carried out by measuring discipline indicators can improve teacher discipline in teaching classes at SD N Jolosutro